2014
DOI: 10.1111/ppa.12230
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of plant and airborne inoculum of Sclerotinia sclerotiorum in spring oilseed rape using real‐time PCR

Abstract: Sclerotinia stem rot of spring oilseed rape (Brassica napus) is caused by Sclerotinia sclerotiorum. In Sweden, the disease leads to severe crop damage that varies from year to year. A real‐time PCR assay was developed and used to determine the incidence of S. sclerotiorum DNA on petals and leaves of spring oilseed rape as well as in air samples, with the aim of finding tools to improve precision in disease risk assessment. Five field experiments were conducted from 2008 to 2010 to detect and study pathogen dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Infection of leaf three sampled at full flowering showed the highest explanation of variation in later SSR incidence. Almquist and Wallenhammar (2015) reported significantly higher incidences of SSR on leaves at lower canopy levels, than on higher levels. Moreover, they detected the pathogen on leaves and not on petals in one field experiment, with a corresponding stem rot incidence of 7%, which suggested that leaves could be an important entry port for Sclerotinia spp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Infection of leaf three sampled at full flowering showed the highest explanation of variation in later SSR incidence. Almquist and Wallenhammar (2015) reported significantly higher incidences of SSR on leaves at lower canopy levels, than on higher levels. Moreover, they detected the pathogen on leaves and not on petals in one field experiment, with a corresponding stem rot incidence of 7%, which suggested that leaves could be an important entry port for Sclerotinia spp.…”
Section: Discussionmentioning
confidence: 99%
“…The use of rapid petal and leaf testing kits to determine petal infections, such as commercialized in Australia (Derbyshire and DentonGiles 2016) are based on culture plates and might need to be substituted by a quantitative or real-time PCR based systems, such as those that detect aerial inoculum levels caught by spore traps in the SYield sensor system from Syngenta (Derbyshire and Denton-Giles 2016). PCR methods for petal and leaf infections, such as published by Ziesman et al (2016), Reich et al (2016) and Almquist and Wallenhammar (2015), should be adapted for large scale use to improve future SSR prediction in the field. Pre-infection treatment before full flowering with the commonly recommended protectant fungicides might be more effective against SSR and more feasible than applying the fungicides during full or late flowering, after determining the risk of infection based on leaf and/ or petal testing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ascospores can germinate on the surface of healthy tissue but cannot infect plants without an exogenous nutrient source (Bolton et al 2006),which often is provided by senescing leaves and petioles or juices flowing from the damaged plants (Kora et al 2003). Thus, flowering is a particularly dangerous moment because senescing flowers serve as nutrient source for the pathogen (Turkington and Morrall 1993;Almquist and Wallenhammar 2015). Direct penetration of fungal hyphae was observed through the cuticle within 12 h from inoculation.…”
Section: Disease Developmentmentioning
confidence: 99%